Prospects for Legal Regulation of the Digitalization Development Program of the Agriculture and Food Industry in the Russian Federation - Abramov, Yury Viktorovich; Zemskov, Yury Viktorovich; Kochetkova, Elena Viktorovna; Lotorev, Evgeniy Nikolaevich; Folomeeva, Tatiana Viktorovna (International Journal of Psychosocial Rehabilitation, 2020)
The urgency of the problem under study is due to issues arising from the lack of proper legal regulation at the legislative level of the process of creating a digital economy as a whole and the digitalization of agriculture, food and processing industries in the Russian Federation, as well as difficulties in the process of theoretical substantiation of these definitions. In this regard, this article is aimed at a comprehensive analysis of the phenomenon of digitalization as a process to create a new product in digital form with new functionality and customer properties, allowing for an economic breakthrough, gaining new competitive advantages in business, going to the construction of Industry 4.0. The leading approach to the study of this problem is to determine the specifics of legal regulation and the presence of a significant number of administrative barriers that impede the initiative in introducing elements of digitalization into individual farms. The article summarizes the problematic issues related to the need to adopt new legislation and make changes to the system and structure of public authorities, as well as the doctrinal approach to the subject matter.